Docking Studies of Some Novel Hetrocyclic Compound as Acat Inhibitors: A Meta Analysis - Aneesa; Kumar, Roshan; Saha, Purabi; E., Keshamma; Sachitanadam, Parkavi; Subramanian, Muthukumar (Journal for Research in Applied Sciences and Biotechnology, 2022)
We use molecular modelling and pharmacological testing to identify TCM compounds that may suppress SQS activity. By utilising previously established SQS inhibitors, ten HipHop pharmacophore models were developed. Finally, we used active medicines to explore other potential anti-hyperlipidemia targets in HepG2 cells and establish whether or not the lipid-lowering effect was due to SQS inhibition. As a potential treatment for hyperlipidemia, this research seeks to identify TCM SQS inhibitors. The rings in a heterocyclic compound are each made up of atoms from a different chemical element. Pyridine, thiophene, pyrrole, and furan are the building blocks for quinoline, benzothiophene, indole, benzofuran, benzthiazole, benzimidazole, and benzoxazole, respectively.